What is the best workflow for an operating room? A simulation study of five scenarios. - Marjamaa RA; Torkki PM; Hirvensalo EJ; Kirvelä OA; Marjamaa, Riitta A; Torkki, Paulus M; Hirvensalo, Eero J; Kirvelä, Olli A (Health Care Management Science, 2009)
Parallel induction of anesthesia improves operating room (OR) efficiency. To support decision-making as to optimal facilities and optimal use of resources, we compared the cost-efficiency of several workflow models of parallel induction to that of the traditional model, using discrete-event simulation. For each scenario, average number of procedures performed, surgery time, daily over- and underutilized time, and staffing costs per operation were assessed. We also studied whether scheduling short and long procedures in separate rooms would amplify the effects of the parallel processing. All parallel work-flow models demonstrated better cost-efficiency than the traditionally sequenced working pattern. Staffing costs per procedure were 7% lower in the best induction model than in the traditional model. When short procedures were scheduled separately, differences between induction models were small.